PERCENTAGE OF BROILER ABDOMINAL FAT GIVEN DRAGON FRUIT PEEL JUICE TROUGH DRINKING WATER - I M. D. A., Saputra; Candrawati, D. P. M. A; Dewi, G.A.M.K. (Jurnal Peternakan Tropika, 2024)
This research aims to determine the effect of dragon fruit peel juice trough drinking water on the percentage of abdominal fat in broiler . The research was conducted in Buahan Village, Tabanan District, Tabanan Regency from November to December 2021.The design used is a Completely Randomized Design (CRD) is use tot ther research with 4 treatments and 4 replications each replicatiaon ucer broiler. Each experimental unit is filled with 4 chickens. The four treatments are chickens given drinking water without dragon fruit peel juice (P0), chickens given 2% dragon fruit peel juice through drinking water (P1), chickens given 4% dragon fruit peel juice through drinking water (P2) and chickens given 6% dragon fruit peel juice through drinking water (P3). The variables observed were pad fat, percentage of pads fat, mesentery fat, ventricular fat and abdominal fat. The results showed that giving dragon fruit peel juice through drinking water to P1, P2 and P3 treatments resulted in a higher slaughter weight than P0. On the percentage of pads fat, mesentery fat and abdominal fat treatment P1, P2, P3 had no significant effect (P>0.05) on P0. Meanwhile, the percentage of ventricular fat treatment of P1, P2, P3 had a significant effect (P<0.05) compared to P0. Based on the results of the study, it can be concluded that giving dragon fruit peel juice in drinking water to broilers aged 35 days had no effect on the percentage of pads fat and mesentery fat, but is able to reduce the percentage of ventricular fat and abdominal fat compared to giving drinking water without dragon fruit peel juice.